How do fraud diamond and procrastination trigger cheating behavior in online learning during the Covid-19 pandemic? - Novita Novita; Firdatul Jannah (Universitas Hayam Wuruk Perbanas, 2022)
The Covid-19 pandemic that hit Indonesia has changed the pattern of the learning system from face-to-face in the classroom to online learning. In practice, the online learning system utilizes information technology, which raises not only effectiveness, but also new challenges. One of the challenges of the online learning system is the student cheating behavior. This study aims to determine the effect of the fraud diamond dimensions, which consist of pressure, opportunity, rationalization, and capability,and procrastination on the detection of student cheating behavior. This research is a quantitative research. The data used is primary data in the form of questionnaires. The respondents of this study are college students at LLDIKTI Region III DKI Jakarta. The data consists of 400 sample students. Data testing is carried out using STATA Version 14.2. The results of this study indicate that the fraud diamond dimensions consisting of pressure, opportunity, rationalization, and capability have a positive effect on the detection of student cheating behavior. Procrastination also has a positive effect on the detection of student cheating behavior.